Genome-wide identification of DNA methylation QTLs in whole blood highlights pathways for cardiovascular disease - Tianxiao Huan (Nature Portfolio, 2019)
Differentially methylated CpGs can inform on disease mechanisms and be useful as biomarkers. Here, the authors perform GWAS for DNA methylation in whole blood, cis- and trans-meQTL mapping, followed by Mendelian randomization analysis that links meQTLs with cardiovascular diseases.